Adiabatic Brownian motor with a stepwise potential perturbed by a dichotomous harmonic sygnal - Shapochkina, Irina V.; Savina, Nastassia D.; Zaytseva, Elena M.; Rozenbaum, Viktor M.; Ikim, Maria I.; Bugaev, Aleksander S. (Journal of the Belarusian State University. Physics, 2021)
We obtained an analytical expression for the average motion velocity of an adiabatic Brownian motor (ratchet), which operates due to small dichotomous spatially harmonic fluctuations of a stepwise potential. The symmetry properties of the average velocity as a functional of the stationary and fluctuating components of the nanoparticle potential energy are revealed, and the ranges of values of the system parameters that ensure the rightward and leftward motion of the motor are determined. We showed that the average motor velocity is a non-monotonic function of the stepwise potential height. For a singular (infinitely high and narrow) potential barrier, the average velocity depends non-monotonically on the «power» of this barrier (the barrier width multiplied by the exponent of the ratio of the barrier height to the thermal energy). The article continues the further development of theoretical methods of symmetry analysis by applying the general approaches proposed by the authors to specific motor systems.
Keywords: diffusion transport; diffusional dynamics; ratchet systems; adiabatic Brownian motors; symmetry; stepwise potential; harmonic fluctuations